PERBANDINGAN DAYA GUNA TERAPIINTENSE PULSE LIGHT AND HEAT ENERGYDENGANJEL BENZOIL PEROKSIDA 2,5% UNTUK AKNE VULGARIS DERAJATRINGAN DAN SEDANG - , TRIASARI OKTAVRIANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Acne vulgaris is a chronic inflammatory disease of pilosebaceous units of the skin characterized by the development of non-inflammatory lesions in the form of blackheads and/or inflammatory lesions such as papules, pustules and nodules. Aetiopathogenesis of acne is multifactorial and the involvement of these factors led to the emergence of variety in acne treatments modality. The use of technology-based light therapies such as intense pulsed light and heat energy (IPL) provides an alternative therapy for patients with acne besides many standard therapies thatalready available, including benzoyl peroxide (BP) gel, which has a similar therapeutic targets, that isP. acnes and the damage of pilosebaceous unit. More research required based on clinical evidence to explain the efficacy and safety of light therapy as well as support on clinical use of light therapy. Objective: To evaluate the efficay of the therapy by comparing the reduction in the number of non-inflammatory lesions, inflammatory lesions and the number of P.acnes in patients with mild and moderate acne vulgaris treated with intense pulsed light and heat energy and benzoyl peroxide gel 2.5%. Methods: The study was conducted with randomized controlled trial parallel design. Subjects were patients with mild and moderate acne vulgaris by using consecutive sampling. Acne severity was determined by the method of Combined Acne Severity Classification (CASC). Statistical analysis using repeated measurement analysis of variance to assess the reduction in lesions and number of P. acnes in each group. Comparison of the difference in the mean reduction in lesion and number of P. acnes between the two treatment groups were statistically analyzed by independent t-test with a significance value of p<0.05. Results: Of the 62 patients, with mild and moderate acne vulgaris, skin types of IV and V were enrolled in this study. Thirty-two patientstreated with IPL